EVALUASI PENGGUNAAN BETON PRECAST DI PROYEK KONSTRUKSI - Aziz Mudzakir Adiasa; Dimas Kurniawan Prakoso; Jati Utomo Dwi Hatmoko; Tanto Djoko Santoso (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Innovative of utilization of precast concrete is growing rapidly lately, one of them is precast plate flyslab. The purpose of this research was to evaluate of utilization of precast concrete compared with conventional concrete in construction projects. Research is aiming to determine the level of use of precast concrete, analyzing the aspect of time, costs, workers, and the environmental impact of the use of precast concrete in building. Implementation method used is the literature study, interviews with the participants construction (contractor, consultant, purveyor and supervisor), and field observations of the four projects building two to three floors, including two residences, one home store and a school building. The results of the comparison between the Flyslab precast plate method with conventional method obtained average reduction as follows : the duration of work between 3,94% - 72,97%, the number of workers between 51,33% - 87,45%, budget-estimate plan between 3,05% - 37,57%, and the reduction use of timber as formwork and scaffolding between 90,11% - 98,81%. Overall utilization of precast Flyslab plate is cheaper, faster, laborers are few, and more friendly to the environment if compared with conventional cast plate in place.